Diversidade florística e funcional em formações florestais ribeirinhas no Triangulo Mineiro, MG, Brasil - Borges, Mariana Prado (2011)
The riparian forests classification as ciliar forest, swamp and non-swamp gallery forest is related to environmental differences that reflect in the floristic diversity of these ecosystems and, probably, influence the functional diversity. These environments, that have high ecological importance, have suffered with degradation caused by human activities and, therefore, restoration and management programs based on ecological communities attributes, including the functional diversity, are important for the conservation. The aims of this paper were: [1] investigate the floristic composition and structure of the swamp gallery forest of Glória stream (Uberlândia MG) and its floristic similarity with others swamp forests in the Cerrado Biome; [2] use reproductive attributes of three types of riparian forests to compare them as the functional diversity. We used the floristic data relating to three areas: ciliar forest of Araguari river, non-swamp gallery forest of Panga stream and the swamp gallery forest of Glória stream, located in Uberlândia, MG, Brazil. To data collection in Glória forest, we used the point-quarter sampling, were taken 70 points along spaced transect, adding 280 individuals with circumference ≥ 15 cm from 1,30 m of the ground. The floristic similarity analyses of 12 swamp forests was done using the Sørensen coefficient. To functional diversity comparisons, the species were classified into functional groups according to attributes reproductive categories (sexual system, dispersal system and pollinators). Differences of reproductive attributes patterns among areas were tested using contingency tables and functional diversity of the areas was calculated using Shannon s index. We found 36 species and 23 families in Glória forest and the Shannon diversity index was 2,67. The species richness and diversity found was similar to others swamp forest in Cerrado. Seven species dominant adding 78,4% of VI. The low diversity and dominance of few species is a feature of swamp forests that, because of restrictive environment imposed by flooding, show high selectivity for establishment of plant species. At similarity analyses, swamp forest areas presented low similarity among them.The patterns of reproductive attributes were similar in several aspects between forests of Araguari river and Panga stream. The Glória stream forest showed patterns differing from the other forests, with seed dispersal exclusively by animals (90% birds), predominantly dioecious individuals, low pollinator diversity and high proportion of generalist pollinators. These differences were attributed as a possible consequence of the environmental characteristics of these ecosystems: environments naturally fragmented and restrictive due to discontinuous and permanent flooding along the watercourses. Glória forest tended to lower functional diversity in relation to others. This study indicates that environmental characteristics which determine the structure and floristics of riparian forests also influence the functional patterns of these ecosystems. However, more detailed studies are needed to better understand the functional ecology of these ecosystems and to contribute to management and conservation of these environments.